Investigation of etching selectivity and microstructure of Ag-doped Sb2Te thin film for dry lithography. (20th January 2022) - Wei, Tao; Shen, Wancheng; Chen, Xingwang; Chen, Lei; Hu, Jing; Cheng, Miao; Liu, Qianqian; Li, Wanfei; Ling, Yun; Wei, Jingsong; Liu, Bo
Abstract: Dry lithography is a promising micro-/nanomanufacturing method owing to its advantages of being solution-free, its absence of undercut and resistance to swelling. However, heat-mode resists suitable for dry lithography are less reported. This work reports on the use of Ag-doped Sb2 Te thin film as a heat-mode resist, and its etching selectivity and microstructures are investigated in detail. It is found that Ag1.44 Sb2.19 Te thin film possesses high etching selectivity in CHF3 /O2 mixed gases and can act as a heat-mode resist. In order to elucidate the mechanism of high etching selectivity, the microstructures of the Ag-doped Sb2 Te thin films are analyzed using x-ray diffraction, Raman spectra, x-ray photoelectron spectroscopy, and transmission electron microscopy methods. The results show that the etching selectivity is attributed to the phase separation of Ag1.44 Sb2.19 Te film and the formation of the Sb phase after laser exposure, leading to a reduction in etching resistance in CHF3 /O2 mixed gases. In addition, pattern transfers from Ag1.44 Sb2.19 Te to SiO2 and Si substrates are achieved successfully and the etching selectivities of Si and SiO2 to Ag1.44 Sb2.19 Te are both higher than 2:1. This work may provide a useful guide for the research of dry lithography without wet development.